Prediction of stone-free status after single-session retrograde intrarenal surgery for renal stones - Tonyalı, Şenol (Turk J Urol, 2018)
OBJECTIVE: To determine the possible factors effecting stone-free status (SFS) after single-session retrograde intrarenal surgery (RIRS) for renal stones. MATERIAL AND METHODS: We retrospectively analyzed the charts of 100 consecutive patients who underwent RIRS. Unilateral procedures performed for single renal stones were included in the study. The studied parameters included patient demographics, stone characteristics (size, volume, location and attenuation according to Hounsfield unit [HU]), operation time, presence of preoperative double-J stent (DJS), use of ureteral access sheath (UAS) and SFS. RESULTS: The study population consisted of 100 patients where 43 of them were stone free and remaining 57 had residual stones. The mean age of the patients was 47.2±13.4 years. The mean stone size (largest dimension), stone attenuation and stone volume were 14.8±5.8 mm, 1010±416 HU and 937±929 mm(3), respectively. The mean operative time was 60.8±24.2 minutes. Mean stone size, volume and HU were higher in the RS group compared to SF group but without any statistically significant difference, 15.2±6.1 vs. 14.2±5.3 mm, 1056±1037 mm(3) vs. 780±745 mm(3) and 1061±374 HU vs. 942±462 HU, respectively (p=0.490, p=0.135 and p=0.226). In multivariate regression analysis stone location and UAS use were found to be the significant predictors of SFS. Patients with lower pole stones are 2.25 times likely to have residual stones after RIRS compared to patient’s having stones at other localizations (p<0.001). CONCLUSION: Stone volume could be a more reliable parameter than stone size in predicting RIRS success. Lower pole stone location and UAS use could be considered the most significant predictors of SFS after single session RIRS for single renal stones.